LANGKAH PEMERINTAH MENGHADAPI 2 TAHUN PUTUSAN MK NOMOR 91/ PUU-XVIII/2020 MENGENAI PENGUJIAN UNDANG-UNDANG CIPTA KERJA (Government’s Step to Face 2 Years of MK Decision Number 91/PUU-XVIII/2020 Concerning About Job Creation Act Testing) - Diani Kesuma; Siti Fatiha Aurelia (Program Magister Ilmu Hukum Universitas Pancasila, 2022)
The Law on Job Creation is promulgated to bring convenience to investorswhich has an impact on the speed of the nation’s economic development. Withthe omnibus law technique, the Job Creation Act has succeeded in cuttingdown several overlapping and long-winded regulations. Like other laws, theestablishment of the Job Creation Law must be in line with what is regulatedthrough the PPP Law. This is a major concern because the omnibus law techniqueis not yet known in the PPP Law, resulting in the Job Creation Act being declaredconditionally unconstitutional. In this case, the Constitutional Court is of theopinion that the Job Creation Law is not in accordance with the mandate of thePPP Law and has also forgotten the involvement of the public in its formation.Therefore, within 2 years of the decision being issued, the government must finda way out so that the Job Creation Law can be enforced as before. This step wastaken by the government by revising the PPP Law by normating the omnibus lawmethod. In addition, there needs to be a spark regarding what form is suitableto bring the community into the formation of the Job Creation Law, consideringthat there is very little time to be able to catch up with the shortcomings of theJob Creation Law